Managing Supply Chain Risk with the Integration of Internet of things in the manufacturing Sector of Pakistan - Kumar, Prince; Aziz, Shahid (2023)
In the ever-evolving landscape of global trade and manufacturing, supply chain resilience has emerged as a vital concern for organizations operating in the manufacturing sector. This research study delves into the critical domain of managing supply chain risk through the integration of Internet of Things (IoT) technologies within the manufacturing sector of Pakistan. With the advent of Internet of Things, the manufacturing industry in Pakistan has witnessed transformative opportunities to enhance operational efficiency and mitigate supply chain vulnerabilities. This qualitative study engaged ten seasoned supply chain professionals through in-depth interviews to discern the multifaceted impact of IoT integration on risk management within the manufacturing sector. The results of this study, analyzed using thematic analysis within Nvivo software, illuminate the implications of using the Internet of Things in supply chain risk management, the aim is to understand how the Internet of things influences and impacts the supply chain risk management process, both internally and externally, and the resulting outcomes. The study is guided by the information processing theory and employs a methodology based on theory to investigate the information requirements and processing capabilities of supply chain risk management supported by the internet of things. The findings of the study reveal that the organizations involved experienced increased data availability, which led to improved process transparency and management. Supply chain risk management also showed enhancements across its various stages, including risk transparency, risk awareness, and risk strategies. These improvements provided a competitive advantage by aligning the information needs with the information processing capabilities. The study provides detailed insights into the structure of internet of things systems, main use cases, and the impact on the supply chain risk management process, offering valuable information for managers. It highlights the benefits of increased data availability, improved process transparency, and management, as well as the implications for personnel and potential barriers. The findings provide valuable insights for Supply chain managers and pave the way for further research in this area.